Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.15740/has/au/11.3/204-208
|View full text |Cite
|
Sign up to set email alerts
|

Impact of women self-help groups (SHGs) on income, employment, investment and saving in south Konkan region

Abstract: The present study entitled, "Impact of women self help groups on income, employment, investment and saving in South konkan Region" was carried out in South Konkan region purposively. From Ratangiri district Dapoli, Khed and Guhaghar while from Sindhudurg district Kudal, Devgad and Kankavali tahsils were selected. From each tahsil, ten SHGs and five members of each SHG were selected randomly. Thus, final sample consisted of 60 SHGs, 300 SHG members. The selected SHGs were categorized taking into consideration g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Hence, we reject the null hypothesis and there was a significant increase in 'Productive working days' of the women entrepreneurs after joining SHG. This finding of the study was in agreement with the findings of Subramanian (2010) and Lagare et al (2016) [17,9] .…”
Section: Change In the 'Productive Working Days' Of The Women Entrepreneurs Of Shgssupporting
confidence: 94%
See 2 more Smart Citations
“…Hence, we reject the null hypothesis and there was a significant increase in 'Productive working days' of the women entrepreneurs after joining SHG. This finding of the study was in agreement with the findings of Subramanian (2010) and Lagare et al (2016) [17,9] .…”
Section: Change In the 'Productive Working Days' Of The Women Entrepreneurs Of Shgssupporting
confidence: 94%
“…Hence, we reject the null hypothesis and there was significant improvement in 'Monthly saving' of the women entrepreneurs after joining SHG. [17,14,10,12,3,9,8,15,18] .…”
Section: Change In the 'Monthly Saving' Of The Women Entrepreneurs Of Shgsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low return from investment, shortage of working capital, seasonal nature of group activity and lack of stability in group, were also identified as a problems faced for effective functioning of Self Help Group. The finding on the study of the problems faced by the Self Help Group (SHG) is in conformity with past study which revealed that, lack of formal education, family responsibilities as their major (personal problem), conflicts, lack of communication skills among the group members in decision making process was the major (social problem), heavy competition is major source of (marketing problem), and insufficient loan as their major (financial problem), among the SHG members in the study area [8,9,10]. Self help groups are instrumental for rural development but are facing numerous problems.…”
Section: Constraints Faced By the Women Self Help Group In Nagalandsupporting
confidence: 53%
“…Many NGOs are promoting the SHG mechanism and linking it to various other development interventions. Whereas there is ample evidence that the SHG approach is a very effective, efficient, and relevant tool for organizing and empowering the poor, do arise with the design, development, and introduction of programs to promote incomegenerating activities (IGAs) that will generate sufficient, sustainable and regular income" [4,5].…”
Section: Introductionmentioning
confidence: 99%